2018
DOI: 10.1186/s12954-018-0236-8
|View full text |Cite
|
Sign up to set email alerts
|

The “here and now” of youth: the meanings of smoking for sexual and gender minority youth

Abstract: BackgroundThe mainstream tobacco field in the USA tends to situate youth as passive, particularly in terms of their susceptibility to industry manipulation and peer pressure. However, failing to acknowledge youths’ agency overlooks important meanings youth ascribe to their tobacco use and how those meanings are shaped by the circumstances and structures of their everyday lives.MethodsThis article is based on analysis of 58 in-depth qualitative interviews conducted with sexual and gender minority youth living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 80 publications
2
39
0
Order By: Relevance
“…While some research addresses how smoking is experienced by different and combined social identities such as gender and race, (non)smoking as social identity is not addressed [ 49 , 50 ]. In light of the emphasis of non-smokers on the smokers’ status in this study, our findings underline the importance of this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…While some research addresses how smoking is experienced by different and combined social identities such as gender and race, (non)smoking as social identity is not addressed [ 49 , 50 ]. In light of the emphasis of non-smokers on the smokers’ status in this study, our findings underline the importance of this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…However, focusing only on the risks might make the smoking habit more attractive to youth. Failing to acknowledge this and focusing only on future risks may lead to losing the opportunity to reach adolescents with tailored interventions such as emphasizing the perceived benefits of quitting in the present 37 . Therefore, as recommended by other studies, the role of perceived social benefits should be considered in such interventions, as well as the need to increase adolescents’ awareness of the addictive nature of nicotine 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Three studies found that LGBTQ (Lesbian, Gay, Bisexual, Transgender, Queer/Questioning) young adults may start smoking due to factors which relate to their sexuality-related stressors, such as the stress of struggling with one’s sexual identity, sexual discrimination, prejudice or bullying [ 51 , 69 , 73 ]. Smoking was perceived as a tool for survival:…”
Section: Resultsmentioning
confidence: 99%